2019
DOI: 10.1111/jcmm.14351
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid: A potent molecule that protects cardiomyocytes from TNF‐α–induced injury via inhibiting NF‐κB and JNK signals

Abstract: The traditional Chinese herb Lonicerae Japonicae Flos has shown significant clinical benefits in the treatment of heart failure, but the mechanism remains unclear. As the main active ingredient found in the plasma after oral administration of Lonicerae Japonicae Flos , chlorogenic acid (CGA) has been reported to possess anti‐inflammatory, anti‐oxidant and anti‐apoptosis function. We firstly confirmed the cardioprotective effects of CGA in transverse aortic constric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 58 publications
1
33
0
1
Order By: Relevance
“…Similar protective effects were observed in cardiomyocytes pretreated with chlorogenic acid (1 µmol/L for 12 h) followed by TNF-α treatment (40 ng/mL for 24 h) [154]. While TNF-α alone increased mPTP and protein expression of cleaved caspase-3 (activated), chlorogenic acid pretreatment completely blunted these effects, which corresponded to a significant attenuation in TNF-α-induced apoptosis.…”
Section: Role Of Polyphenols In Cardiac Mitochondrial Dysfunctionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar protective effects were observed in cardiomyocytes pretreated with chlorogenic acid (1 µmol/L for 12 h) followed by TNF-α treatment (40 ng/mL for 24 h) [154]. While TNF-α alone increased mPTP and protein expression of cleaved caspase-3 (activated), chlorogenic acid pretreatment completely blunted these effects, which corresponded to a significant attenuation in TNF-α-induced apoptosis.…”
Section: Role Of Polyphenols In Cardiac Mitochondrial Dysfunctionsupporting
confidence: 63%
“…Further illustrating the multiple targets of phenolic acids, cardiomyocytes treated with TNF-α alone (40 ng/mL) for 24 h were apoptotic compared to control. Nonetheless, these apoptotic effects were completely blunted by pretreatment with chlorogenic acid (1 µmol/L) for 12 h [154]. Further, NF-κB phosphorylation was increased due to TNF-α treatment; however, chlorogenic acid reduced NF-κB phosphorylation to control levels.…”
Section: Phenolic Acidsmentioning
confidence: 93%
“…Furthermore, Kang et al (28) revealed that CGA derived from coffee impaired colorectal cancer cell metastasis by suppressing NF-κB, MEK and T-LAK cell-originated protein kinase. Additional studies indicated that CGA could attenuate LPS-induced acute kidney injury, protect cardiomyocytes and ameliorate lead-induced renal damage via suppressing the NF-κB signaling pathway (29)(30)(31). Considering the important role of NF-κB in breast cancer, it was hypothesized that CGA, a potent NF-κB signaling inhibitor, may be a potential drug for clinical therapy of breast cancer.…”
Section: Chlorogenic Acid Induces Apoptosis Inhibits Metastasis and mentioning
confidence: 99%
“…Later in 2019, it was reported that chlorogenic acid improved NO bioavailability and eventually improved blood pressure in cyclosporine induced hypertensive rats (Agunloye et al, 2019). Besides, chlorogenic acid also protects cardiomyocytes from TNF-α-induced injury via inhibition of NF-κB and JNK signals (Tian et al, 2019). Chlorogenic acid supplementation in high-carbohydrate, high-fat diet-fed rats resulted in reduced visceral fat, especially abdominal circumference and retroperitoneal fat.…”
Section: Chlorogenic Acidmentioning
confidence: 99%